Phosphorescent trinuclear gold (I) pyrazolate complex bearing photochromic azobenzene side-chains - Goh, Cheow Kat (2019)
Photochromic soft materials have received particular attention for inducing excellent properties in many fields such as displays, sensor, energy, catalysts, molecular electronics, and memory. In particular, organometallic compounds such as Group 11 azolate complexes with luminescent properties reveal promising characteristics from supramolecular self-assembly of columnar nanostructures upon ultraviolet and visible light treatments. Although self-assembled nanostructures with azobenzene moieties have been used to study photochromic cis-trans isomerization towards light irradiation, there is no example for the utilization at the side-chains of the metal complexes. Herein, this study reports the first successful synthesis of phosphorescent trinuclear gold(I) pyrazolate complex bearing hydrophobic azobenzene side-chains. The gold complex (7) was synthesized via seven stepwise reactions and named as tris[(E)-3,5-dimethyl-4-(4-((4-propoxyphenyl)diazenyl) benzyl)-1H-pyrazolato-N,N’]trigold(I) (7, 28%). Compound 7 showed cis-trans isomerization upon UV and visible light irradiation at 365 nm and 535 nm, respectively. Interestingly, metal-metal interaction was not affected by the cis-trans photoisomerization. Compound 7 showed emission of a combination of 423, 472 and 537 nm with excitation wavelength of 271 nm, large stoke shift of 266 nm suggested the emission to be phosphorescence. Compound 7 was able to show white phosphorescence in dried solid state, which was resulted from the region of blue, green and red emission. Compound 7 was non-emissive in CHCl3, but able to regain emission upon addition of water which decreased the solubility of compound 7 in CHCl3. Successful formation of metal-metal interaction directly related to the phosphorescence of compound 7, which can be utilized as aggregation-induced emissive (AIE) material with photochromic properties.